Evaluation of four commercial DNA extraction kits for the detection of Microsporidia and the importance of pretreatments in DNA isolation - Çetinkaya, Ülfet; Charyyeva, Arzuv; Sivcan, Eda; Gürbüz, Esra (Acta parasitologica, 2018)
Microsporidia are obligate intracellular parasitic protozoa infecting the wide variety of hosts and are commonly known as a cause of chronic diarrhea particularly in immunocompromised individuals. Molecular-based tests have high sensitivity and specificity in disease diagnosis. However, these tests' performance relies on the isolation of DNA in a good concentration. The standard procedures of commercial DNA extraction kits are usually insufficient for this purpose due to the tough walls of spores. This study aimed to test the significance of pretreatments by glass beads and freeze-thawing processes in DNA isolation from microsporidia spores. The parasite was cultured in growing Vero cells and seven serial dilutions were prepared from the collected spores. DNA purification was performed according to different tissue kits and stool kit procedures with and without any pretreatment. Concentration of isolated DNA samples were evaluated by real-time PCR. As a result of this study, the detectable amount of spores is minimum 10 spores in each 100 μ! sample according to the different tissue kits' standard protocols. However, according to the DNA stool mini kit, the detectable amount of spores was found to be 1,000 spores/100 μl of stool sample when pretreated with both the freeze-thawing and glass beads methods.In conclusion, the current study demonstrated that further pretreatments are an essential process for DNA extraction from the stool specimens in order to avoid possible false negativity in the diagnosis of microsporidiosis.
Keywords: DNA fungální; Chlorocebus aethiops; mikrosporidióza; DNA, Fungal; Microsporidia; reagenční diagnostické soupravy; Sensitivity and Specificity; senzitivita a specificita; feces; zmrazování; glass beads; Freezing; Spores, Fungal; Vero buňky; Microsporidiosis; zvířata; spory hub; molekulární biologie; Feces; Cercopithecus aethiops; Enterocytozoon; Real-Time Polymerase Chain Reaction; pretreatment; Reagent Kits, Diagnostic; DNA extraction; Animals; Molecular Biology; freeze-thawing; kvantitativní polymerázová řetězová reakce; Vero Cells